Differential Pulse Polarographic Determination of Atorvastatin in Pharmaceutical Dosage Forms Using Dropping Mercury Electrode - Aziz Ramadan, Abdul; Mandil, Hasna; Hafez, Baraa (Asian Journal of Chemistry, 2013)
New, simple and rapid differential pulse polarographic analysis by using dropping mercury electrode with negative amplitude pulse was developed for determination of atorvastatin in pure and pharmaceutical dosage forms in borax buffer at pH 7.5. One reduction peak was observed in the range -1310 to -1340 mV (Ep). The peak current Ip is linear over the ranges 2-60 μmol L-1. The differential pulse polarographic analysis has been used successfully for the determination of atorvastatin in pure form and in pharmaceutical formulations. The relative standard deviation did not exceed 3.8 % for the concentrations of atorvastatin 2.00 μmol L-1 (1.117 μg mL-1). Regression analysis showed a good correlation coefficient (R2 = 0.9994) between Ip and concentration over the range of 1.117 to 33.52 μg mL-1. The limit of detection and the limit of quantification were 0.129 μg mL-1 and 0.390 μg mL-1, respectively. The proposed method was successfully applied to the analysis of atorvastatin in pure and pharmaceutical dosage forms with average recovery of 97.2 to 104.2 %. The results obtained agree well with the contents stated on the labels.